Peculiarities of spatial structure, floristic similarity and phytocoenic activity of herbaceous plant species in afforestations and natural steppe groups of Southern Kryvyi Rih area - Shevchuk, N. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2019)
The spatial structure, phytocoenic activity, frequency of occurrence and floristic similarity of herbaceous and shrub tiers have been studied in different-aged (30–50 years) afforestations of five species (Gleditsia triacanthos L., Quercus robur L., Robinia pseudoacacia L., Pinus pallasiana D. Don, P. sylvestris L.) and steppe communities of Southern Kryvyi Rih area. It was shown that the spatial structure, floristic similarity in the number of species and phytomass in these afforestations depends on the composition of tree species, their age and the type of light structure. During studying the spatial and storey structure of tree plantations it has been found that multi-storeyness is characteristic for the different ages oakeries. The second storey consists of an artificially planted undergrowth. In the stands of Gleditsia triacanthos, the second storey is not developed, and, in artificial pine forests at the sand arenas, the undergrowth is practically absent. The spatial structure of the national-significant nature monument "Natural Landmark Stepok" depends on the mesophytization and ruderalization of the communities, which are the result of a long and complete reservation. It leads to the increase of the areas of Bromopsideta inermis, Poeta angustifoliae formations and the community with domination of Galium aparine L. During the studying steppe phytocoenoses, it has been found that similarity of their floristic compositions depends on the pasture degeneration (slope steppes), and similarity of their phytomasses depends on the dominant species in phytocoenoses. In forest plantations and steppe communities, the largest number of species has a low occurrence rate (up to 20%) and phytocoenic activity by projective coverage up to 1%. In forest and steppe communities, only dominant species have constant phytocoenotic activity of species by phytomass over the years. In general, the species composition of forest stands, their age and light structure affect in different ways the spatial structure, phytocoenic activity by the projective cover and phytomass of species that spontaneously emerge in the stands.